Incorporating higher-order thinking in the language classroom: English language teachers' perceptions and practices - Moorthi, Sachithanantham Tachina (2017)
Purpose - Higher-order thinking is deemed crucial for students to confront the challenges of the 21st century (R. Collins, 2014).In this connection, Malaysia had proposed transformation to its education system geared towards strengthening its students’ higher-order thinking skills (Malaysian Education Blue Print, 2013-2025).Practising teachers, therefore, need to develop new approaches and strategies to successfully manage these new developments. However, teacher beliefs and practices are found to affect teachers’ strategies for coping with these changes and the challenges that accompany (OECD, 2009).Research has shown that teachers’ perceptions including teacher beliefs, previous knowledge and teacher practices are linked to the actual instruction provided by teachers in the classrooms.T.H. Thu (2009) postulates that teacher beliefs can cause resistance to change, and can greatly influence the teaching and learning process.Banda (2005) found that teacher perceptions of classroom assessment have influence on their classroom assessment practices and that teachers’ academic qualifications seemed to influence teachers’ flexibility to changes. S.Pitiporntapin & T. D. Sadler (2015) postulates that previous teaching perceptions of teachers tend to influence their teaching practices. However, none of the above studies have investigated teachers’ perception and practices of incorporating higher-older thinking skills in a language classroom. While, teaching higher-order thinking in Science and Mathematics may be quite common, teaching those skills in a language classroom may pose difficulties to English language teachers.As such, it is important to investigate the perceptions and practices of the English language teachers to determine their readiness and whether they are equipped to incorporate HOTS in their language classrooms. This study attempts to investigate the English Language teachers’ perceptions and practices as well as the factors that influence them.The objectives of the study are: (i) to provide a better understanding of the English language teachers’ perceptions and practices of incorporating HOTS in their language classrooms, and (ii) to elucidate factors affecting their perceptions and practices of this approach.